2016
DOI: 10.1002/pc.23964
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of modified hydrotalcite on improving the fire resistance of ethylene vinyl acetate containing intumescent flame retardants

Abstract: The NH2 SO3−1 intercalated MgAl‐LDH (SA‐LDH) was prepared and then introduced into ethylene vinyl acetate (EVA) in association with intumescent flame retardants (IFR) in order to improve the flame retardancy of the composite. The structure and thermal stability of SA‐LDH was characterized by Fourier transform infrared, X‐ray diffraction, transmission electron microscopy, and thermogravimetry analysis. The flame retardancy of EVA composite was evaluated by limiting oxygen index (LOI), vertical burning UL‐94, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Thus, many people have done a lot of research on multi‐component flame retardant, such as that the flame‐retardant polylactic acid (PLA) composite was successfully prepared by combining Mg/Al‐LDH–intercalated phosphotungstic acid (PWA‐LDH) with intumescent flame retardant (IFR), and the results showed that the composite added with 18.0 wt% IFR and PWA‐LDH 2.0 wt% passed the UL‐94 V‐0 rating . Similarly, the Mg/Al‐LDH–intercalated by NH 2 SO 3 −1 was also loaded into ethylene vinyl acetate (EVA) with IFR, and the result declared that the pHRR value was declined clearly . Anything else, Ehsan Naderi Kalali et al synthesized phytic acid‐modified LDH (Ph‐LDH) by a one‐step coprecipitation method, and the flame‐retardant PP composites were prepared via combining with ammonium polyphosphate and Ph‐LDH, which proved that there are rarely effects on the impact and tensile properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many people have done a lot of research on multi‐component flame retardant, such as that the flame‐retardant polylactic acid (PLA) composite was successfully prepared by combining Mg/Al‐LDH–intercalated phosphotungstic acid (PWA‐LDH) with intumescent flame retardant (IFR), and the results showed that the composite added with 18.0 wt% IFR and PWA‐LDH 2.0 wt% passed the UL‐94 V‐0 rating . Similarly, the Mg/Al‐LDH–intercalated by NH 2 SO 3 −1 was also loaded into ethylene vinyl acetate (EVA) with IFR, and the result declared that the pHRR value was declined clearly . Anything else, Ehsan Naderi Kalali et al synthesized phytic acid‐modified LDH (Ph‐LDH) by a one‐step coprecipitation method, and the flame‐retardant PP composites were prepared via combining with ammonium polyphosphate and Ph‐LDH, which proved that there are rarely effects on the impact and tensile properties.…”
Section: Introductionmentioning
confidence: 99%
“…One of the alternatives to reduce the flammability is the addition of commercial flame retardants, such as the intumescent systems. Although this type of system has been reported in the literature since 1938, it is still an attractive topic and represents an area of great scientific interest (Ding et al, ; S. Zhang, Tang, et al, ). Along the heating process, the intumescent systems form a swollen protective carbonaceous surface layer called char (Laoutid, Bonnaud, Alexandre, Lopez‐Cuesta, & Dubois, ; Lewin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from its structural properties, PGS has drawn emerging interest as a potential alternative to conventional sorbents . As for other applications of clay‐based materials, sepiolite, montmorillonite, and hydrotalcite can be used as flame retardant to improve flame retardance of the polymers dramatically. As one of the core candidates, the flame retardancy applications of PGS were also well considered .…”
Section: Introductionmentioning
confidence: 99%